Starch-based degradable food packaging bag and preparation method thereof

By forming covalent cross-links and hydrogen bonds between the two modified compounds and starch molecules, the problems of poor water resistance, insufficient mechanical properties and single function of starch-based packaging materials are solved, and the preparation of degradable food packaging bags with high barrier properties, antibacterial properties and thermal stability is achieved, which expands the application scenarios and ensures environmental protection.

CN120795423AInactive Publication Date: 2025-10-17QINGDAO RUIFA PACKAGING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511226277.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-29
Publication Date
2025-10-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing starch-based biodegradable food packaging materials have problems such as poor water resistance, insufficient mechanical properties, single function, and weak binding force between traditional modifiers and starch, making it difficult to meet the diverse needs of food packaging.

Method used

Two modified compounds, N-(2,3-epoxypropyl)-dodecanoyl aspartate and 3-(allyloxy)-2-hydroxypropyltrimethylsilyl chloride, are used to form covalent cross-links and hydrogen bonds with starch molecules to improve the hydrophobicity, thermal stability and antibacterial properties of the material, and to prepare biodegradable food packaging bags with high barrier properties, water resistance and mechanical strength.

Benefits of technology

It significantly improves the water resistance and mechanical properties of starch-based materials, imparts multifunctionality, broadens the scope of application, and ensures that the material has no harmful residues after degradation. It is suitable for the packaging of fresh fruits and vegetables, ready-to-eat meat and baked goods.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a starch-based degradable food packaging bag and a preparation method of the starch-based degradable food packaging bag, and belongs to the field of degradable high polymer materials. According to the present invention, with cooperation of glycerol, two brand new modified compounds such as N-(2, 3-epoxypropyl)-dodecanoyl aspartate and 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride, ammonium persulfate and ascorbic acid, the compound is prepared. Wherein the N-(2, 3-epoxypropyl)-dodecanoyl aspartate is prepared by the following steps: carrying out acylation reaction on L-aspartic acid and dodecanoyl chloride in tetrahydrofuran, then carrying out cyclization reaction on the obtained product and epoxy chloropropane under the action of potassium carbonate, and carrying out precipitation and drying to obtain the N-(2, 3-epoxypropyl)-dodecanoyl aspartate. Through the synergistic effect of the two modified compounds, the water resistance, mechanical properties and functional diversity of the starch-based material are improved, meanwhile, good degradability is kept, and the starch-based material is suitable for food packaging scenes.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of degradable high molecular materials, in particular to a starch-based degradable food packaging bag and a preparation method thereof. BACKGROUND

[0002] Starch-based degradable food packaging materials have become a research hotspot and industrial direction for replacing traditional petroleum-based plastic packaging due to their wide raw material sources, complete biodegradability, and environmental friendliness. Such materials use natural starch as the main film-forming matrix, and have the characteristics of renewability and low environmental load, and are particularly suitable for fresh fruits and vegetables, instant food, baked products, and other scenarios that have specific requirements for the gas permeability and barrier properties of packaging materials. However, the strong hydrogen bonding between starch molecular chains results in high crystallinity and poor thermoplasticity, making it difficult to directly process into film materials that meet the requirements of food packaging. At the same time, starch itself has strong hydrophilicity and is prone to swelling and rapid mechanical property degradation after water absorption, limiting its application in high humidity environments. In addition, traditional starch-based materials have single functions and lack key properties such as antibacterial and heat sealing properties, making it difficult to meet the demand for diversified functions of modern food packaging. These inherent defects have become the core bottleneck restricting the large-scale application of starch-based packaging materials.

[0003] Existing modification techniques for starch-based packaging materials mainly include physical blending and chemical modification. Physical blending improves the processability and mechanical properties of starch by adding plasticizers, nanofillers, or degradable polymers. However, plasticizers are prone to migration and precipitation due to high temperature or long-term storage, leading to material brittleness and performance degradation over time. Nanofillers have poor interfacial compatibility with starch and require additional surface treatment to improve dispersion, increasing process complexity and cost. The blending system of degradable polymers and starch is prone to phase separation due to thermodynamic incompatibility, affecting the uniformity and transparency of the film. Chemical modification introduces polar or non-polar groups on the starch molecular chain through esterification, etherification, grafting copolymerization, and other reactions to improve its hydrophobicity, thermal stability, or reactivity. However, traditional modifiers are mostly general small molecules or oligomers, and the interaction between them and starch molecules is mainly weak hydrogen bonding, with limited binding force. Some modifiers contain hydrophobic long carbon chains, which can improve water resistance but may reduce the biocompatibility of the material. In addition, a single modifier can usually only solve a specific problem and is difficult to endow starch-based materials with multiple functional characteristics, making it difficult to meet the high requirements of food packaging for comprehensive performance.

[0004] With the continuous growth of the demand for green, functional and high-performance materials in the food packaging industry, it is an urgent need to develop a starch-based packaging material with high barrier property, water resistance, thermal stability and multifunctionality. The limitations of traditional modification techniques show that it is difficult to break through the performance bottleneck of starch-based materials through simple blending or single functional group modification, and it is necessary to develop new structural modified compounds from the aspect of molecular design to form strong covalent bonds or hydrogen bonds with starch molecules to achieve the synergistic improvement of multiple properties. The two new modified compounds (N-(2,3-epoxypropyl)-dodecanoyl aspartate and 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride) proposed in the application form a double combination of covalent cross-linking and hydrogen bonding with starch molecules by introducing long-chain alkyl, epoxy group, carboxyl and silane group, hydroxyl, allyl and other multi-functional groups, and at the same time endow the material with key properties such as hydrophobicity, thermal stability, antibacterial property, etc., effectively solving the problems of poor water resistance, insufficient mechanical property and single function of traditional starch-based materials, and providing a new technical path for the industrial application of starch-based degradable food packaging materials. SUMMARY

[0005] The present application aims to provide a starch-based degradable food packaging bag and its preparation method, which solves the technical problems of poor water resistance, insufficient mechanical property, single function, weak combination of traditional modifiers and starch, and easy to leave harmful substances after degradation of the existing starch-based degradable food packaging material.

[0006] The present application realizes the above-mentioned purpose through the following technical solutions: A starch-based degradable food packaging bag, comprising the following raw materials by weight: Pretreated potato starch: 80-120 parts by weight; Glycerol: 8-12 parts by weight; N-(2,3-epoxypropyl)-dodecanoyl aspartate: 5-9 parts by weight; 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride: 3-7 parts by weight; Ammonium persulfate: 0.08-0.15 parts by weight; Ascorbic acid: 0.02-0.06 parts by weight; The preparation method of the N-(2,3-epoxypropyl)-dodecanoyl aspartate comprises: A1, mixing L-aspartic acid with anhydrous tetrahydrofuran, adding dodecanoyl chloride at 0-5℃, adding NaHCO3 aqueous solution, filtering and drying to obtain N-dodecanoyl-L-aspartic acid; A2, dissolving N-dodecanoyl-L-aspartic acid in acetone, adding epichlorohydrin, reacting at 60-64℃ under the action of K2CO3, and then precipitating with diethyl ether, washing and vacuum drying.

[0007] In the present application, the synthesis of N-(2,3-epoxypropyl)-dodecanoyl aspartate takes L-aspartic acid as a starting material, and the amino group (-NH2) in the molecule has strong nucleophilicity, which can react with the acyl group (-CO-Cl) of dodecanoyl chloride to form an amide bond (-CONH-), thereby generating an N-dodecanoyl-L-aspartic acid intermediate. Subsequently, the hydroxyl group (-OH) in the intermediate molecule is dissociated into an oxygen anion (-O - ) under the alkaline conditions of potassium carbonate, which exhibits strong nucleophilicity and reacts with the epoxide group (three-membered ring structure) of epichlorohydrin to release ring tension and form a new ether bond (-O-), thereby obtaining N-(2,3-epoxypropyl)-dodecanoyl aspartate containing an epoxypropyl side chain. In this process, the introduction of the dodecanoyl group endows the molecule with strong hydrophobicity, and the epoxypropyl group provides a reaction site for subsequent covalent cross-linking with starch.

[0008] According to a preferred embodiment of the present application, in step A1, the reaction time is 3-5 h at 0-5℃.

[0009] According to a preferred embodiment of the present application, in step A2, the reaction time is 4-6 h at 60-64℃, and the temperature for vacuum drying is 40-42℃, and the time is 12-14 h.

[0010] According to a preferred embodiment of the present application, the preparation method of the 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride comprises: B1, mixing 3-chloro-2-hydroxypropyl trimethylsilane with anhydrous ethanol, adding allyl alcohol, and then adding NaOH to adjust the pH to 10-11, and stirring at 70-72℃; B2, after the reaction is completed, vacuum distillation is performed, and anhydrous sodium sulfate is used for drying.

[0011] In the present application, 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride is synthesized by taking 3-chloro-2-hydroxypropyl trimethylsilane as a raw material, and the chlorine atom (-Cl) in the molecule is connected to one end of the propyl chain, and the other end is a trimethylsilyl group (-(CH3)3Si-). In the polar solvent of anhydrous ethanol, the pH of the system is adjusted to 10-11 by sodium hydroxide, so that the hydroxyl group (-OH) of allyl alcohol is dissociated into an oxygen anion (-O -The oxygen anion attacks the carbon atom of the chlorine atom of 3-chloro-2-hydroxypropyl trimethylsilane as a nucleophile, a nucleophilic substitution reaction (SN2 mechanism) occurs, the chlorine atom is replaced by an allyloxy group (-OCH2CH=CHCH2-), and 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride is generated. In this process, the introduction of trimethylsilyl improves the hydrophobicity and thermal stability of the molecule, the double bond (C=C) of the allyloxy group provides active sites for the subsequent radical crosslinking reaction, and the hydroxyl group enhances the interfacial bonding through hydrogen bonding with the starch molecule.

[0012] According to the preferred embodiment of the present application, in step B1, the stirring reaction time at 70-72℃ is 5-10h.

[0013] According to the preferred embodiment of the present application, in step B2, the temperature of the reduced pressure distillation is 60-64℃; and the drying time is 2-4h.

[0014] The present application also provides a preparation method of the starch-based degradable food packaging bag, and the steps include: S1, taking potato starch, adding deionized water, and magnetically stirring at 94-96℃ to gelatinize; adding α-amylase reaction, centrifuging after enzyme inactivation, and freeze-drying the obtained precipitate to constant weight, crushing and sieving to obtain pretreated starch; S2, adding pretreated starch, glycerol, N-(2,3-epoxypropyl)-dodecanoyl aspartate, and 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride into a high-speed mixer to obtain a blend; S3, adding ammonium persulfate and ascorbic acid to the blend and continuing to mix; transferring to a twin-screw extruder, melt blending, and then water cooling and granulating to obtain a starch-based composite master batch; drying the master batch in a vacuum drying oven, and then adding it to a film blowing machine to blow a film.

[0015] In the present application, the preparation reaction mechanism of the starch-based packaging bag; in the pretreatment stage, the potato starch is absorbed in hot water and swells, the crystalline region is destroyed, the gelatinization reaction occurs, the molecular chain is converted from the ordered helical structure to the disordered amorphous structure, and the glass transition temperature of the starch is reduced; the alpha-amylase specifically cuts the alpha-1, 4 glycosidic bond in the starch molecule, and the long-chain starch is decomposed into short-chain dextrin and maltose, further reducing the molecular weight and increasing the reaction activity. In the blending stage, the pretreated starch is mixed with glycerol (a plasticizer), the hydroxyl groups of glycerol and the hydroxyl groups of starch form hydrogen bonds, weaken the hydrogen bond interaction between starch molecules, and improve the flexibility and processing fluidity thereof; two modifiers (N-(2, 3-epoxypropyl)-dodecanoyl aspartate and 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride) form hydrogen bonds with starch molecules through their respective polar groups (such as hydroxyl, epoxy), and are preliminarily adsorbed on the surface of starch particles. In the crosslinking stage, ammonium persulfate is decomposed by heat to generate sulfate radicals, which initiate the radical polymerization reaction of the double bonds (such as the C=C of the allyloxy group) in the modifier, and at the same time, the ring-opening copolymerization of the epoxy groups in the modifier and the hydroxyl groups of the starch occurs, forming a three-dimensional crosslinked network structure; ascorbic acid acts as an antioxidant to inhibit the excessive oxidative degradation of the radical to the starch molecular chain. In the double screw extrusion process, the materials are fully mixed under the action of high temperature (130-150 DEG C) and shearing, and the crosslinked network is further densified; when blowing film, the molten starch-based material is extruded through the die, solidified into a film under air cooling, and finally forms a degradable food packaging bag with high barrier property, water resistance and mechanical strength. In the whole process, the two modified compounds optimize the performance of the starch-based material through covalent crosslinking and hydrogen bonding, ensuring that it meets the functional requirements of food packaging.

[0016] According to the preferred embodiment of the present application, in step S1, the gelatinization time is 40-60 min; the reaction time of adding alpha-amylase is 1.5-2 h.

[0017] According to the preferred embodiment of the present application, in step S2, the mixing time is 20-30 min.

[0018] According to the preferred embodiment of the present application, in step S3, the continuous mixing is added for 10-20 min; the barrel temperature of the double screw extruder is 130-150 DEG C, and the screw rotation speed is 200-300 rpm.

[0019] The present application has the following advantages: The present application has the following advantages:

[0020] Firstly, the multi-dimensional interaction of the two modified compounds with starch molecules significantly improves the water resistance and mechanical properties of the material. Traditional starch-based materials have high crystallinity and strong hydrophilicity due to strong hydrogen bonding between molecular chains, which leads to swelling and deformation after water absorption, and the mechanical strength is difficult to meet the packaging requirements. In this invention, N-(2,3-epoxypropyl)-dodecanoyl aspartate molecules contain long-chain dodecanoyl and epoxy groups. The long-chain alkyl group reduces the surface polarity of starch through hydrophobic interaction, and the epoxy group undergoes ring-opening copolymerization with starch hydroxyl groups to form covalent cross-linking, constructing a stable three-dimensional network structure. The trimethylsilyl group in 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride molecules further reduces the surface energy of the material through steric hindrance effect, and the hydroxyl group forms hydrogen bonds with the starch hydroxyl group to enhance the interfacial bonding, and the allyloxy group participates in the free radical crosslinking reaction. The synergistic effect of the two modifiers makes the hydrogen bonding between starch molecular chains partially replaced by covalent bonds and hydrophobic interactions, significantly reducing the water absorption rate of the material.

[0021] Secondly, the multifunctionality of the two modified compounds gives the material more comprehensive food packaging applicability. Traditional starch-based materials have single function and can only meet the basic packaging requirements, making it difficult to cope with complex scenarios such as fresh fruit and vegetable preservation and baked food packaging. In this invention, the aspartic acid residue of N-(2,3-epoxypropyl)-dodecanoyl aspartate contains a polar carboxyl group that can improve the thermal stability of the material by chelating metal ions, allowing the packaging material to remain structurally stable in high-temperature environments such as heat sealing processes. The chloride ion of 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride has antibacterial activity and can disrupt the ion balance of bacterial cell membranes, effectively extending the shelf life of food. In addition, the introduction of trimethylsilyl group also improves the oil resistance and chemical resistance of the material, making it suitable for the packaging of food containing oil. The synergistic effect of the two modifiers makes the material have high barrier property, antibacterial property, thermal stability and oil resistance, which can be widely used in the packaging of fresh fruits and vegetables, instant meat, baked cakes and other foods, significantly expanding the market application range of starch-based packaging materials.

[0022] Finally, the green design and process compatibility of the modified system ensure the degradability and industrial transformation potential of the material. Traditional modification techniques often introduce non-degradable petroleum-based small molecules or high-risk solvents, resulting in harmful substances remaining after material degradation, or increasing energy consumption and cost due to harsh process conditions. In this invention, both modified compounds are made from renewable resources such as natural amino acids, long-chain fatty acids, and silanes, and their molecular structures only contain carbon, hydrogen, oxygen, and silicon elements. During the degradation process, they can be completely decomposed by microorganisms into water and carbon dioxide, leaving no microplastics or other harmful residues. The solvents used in the preparation process are completely removed through distillation or washing, and the residual amount of solvents in the finished product meets the safety standards for food contact materials. DETAILED DESCRIPTION

[0023] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.

[0024] Glycerol was purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd. (mainly engaged in chemical raw materials and fine chemicals).

[0025] L-aspartic acid was purchased from Wuhan Yuancheng Gongchuang Technology Co., Ltd. (focusing on the research and development and production of amino acids and their derivatives).

[0026] Anhydrous tetrahydrofuran was purchased from Tianjin Xiens Biochemical Technology Co., Ltd. (providing high-purity organic solvents).

[0027] Dodecanoyl chloride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (covering the field of organic reagents).

[0028] NaHCO3 aqueous solution was purchased from Shandong Haihua Co., Ltd. (a large state-owned chemical enterprise that produces soda ash and baking soda).

[0029] Acetone was purchased from Jiangsu Huachang Chemical Co., Ltd. (mainly engaged in basic chemical raw materials).

[0030] Epichlorohydrin was purchased from Shandong Binhua Group Co., Ltd. (a leading domestic propylene oxide company).

[0031] K2CO3 was purchased from Inner Mongolia Yuanxing Energy Co., Ltd. (leading in potassium carbonate production capacity).

[0032] Diethyl ether was purchased from Tianjin Fuchen Chemical Reagent Co., Ltd. (a professional chemical reagent supplier).

[0033] Ammonium persulfate was purchased from Hebei Jiheng Sairui Chemical Co., Ltd. (specializing in persulfate chemicals).

[0034] Ascorbic acid was purchased from Northeast Pharmaceutical Group Co., Ltd. (a long-established pharmaceutical company and a major vitamin C producer).

[0035] 3-Chloro-2-hydroxypropyltrimethylsilane was purchased from Hubei Jusheng Technology Co., Ltd. (a manufacturer of silicone derivatives).

[0036] Anhydrous ethanol was purchased from Jiangsu Lianhai Biotechnology Co., Ltd. (a biomass energy and fine chemical company).

[0037] Allyl alcohol was purchased from Jiangsu Feixiang Chemical Co., Ltd. (a well-known company in the field of fine chemicals).

[0038] NaOH was purchased from Shandong Haihua Co., Ltd. (supplier of caustic soda and basic chemical raw materials).

[0039] Anhydrous sodium sulfate was purchased from Sichuan Chuanmei Special Salt Co., Ltd. (a leading enterprise in the Yuanming powder industry).

[0040] Potato starch was purchased from Zhongliang Biochemical Energy Co., Ltd. (a subsidiary of COFCO Group, a backbone enterprise in starch processing).

[0041] Alpha-amylase was purchased from Shandong Blue Bio-technology Co., Ltd. (a listed enterprise in the enzyme preparation industry).

[0042] High-speed mixer was purchased from Zhangjiagang Wanplast Machinery Co., Ltd. (specializing in the research and development and manufacturing of plastic machinery).

[0043] Double-screw extruder was purchased from Nanjing Keya Chemical Equipment Co., Ltd. (a supplier of polymer material processing equipment).

[0044] Film blowing machine was purchased from Rui'an Jinbang Machinery Co., Ltd. (a professional manufacturer in the field of packaging machinery).

[0045] Example 1 Preparation of N-(2,3-epoxypropyl)-dodecanoyl aspartate: L-aspartic acid 10 g was weighed into 50 mL of anhydrous tetrahydrofuran and stirred to dissolve. The temperature of the solution was lowered to 3°C, and dodecanoyl chloride 12 g was slowly added. The temperature was maintained for 4 h. After the reaction was completed, 100 mL of 5 wt% NaHCO3 aqueous solution was added, and stirred for 10 min before being filtered. The filter cake was collected and dried in a vacuum drying oven at 41°C for 13 h to obtain N-dodecanoyl-L-aspartic acid 10.5 g. The above intermediate 10 g was dissolved in 50 mL of acetone, and epichlorohydrin 6 g and K2CO3 5 g were added. The temperature was raised to 62°C and reacted for 5 h. After the reaction was completed, the solution was poured into 200 mL of diethyl ether to precipitate, and the precipitate was collected and dried in a vacuum drying oven at 41°C for 13 h to obtain N-(2,3-epoxypropyl)-dodecanoyl aspartate.

[0046] Preparation of 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride: 3-chloro-2-hydroxypropyl trimethylsilane 15 g, anhydrous ethanol 50 mL, and allyl alcohol 5 g were weighed into a round-bottom flask, stirred to dissolve, and then NaOH 2 g was slowly added. The pH of the system was adjusted to 10.5, and the temperature was raised to 71°C and stirred for 7 h. After the reaction was completed, the ethanol was removed by distillation under reduced pressure at 62°C. The remaining material was dried with anhydrous sodium sulfate 2 g for 3 h, and filtered to obtain 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride.

[0047] Preparation of starch-based degradable food packaging bag: 100 g of potato starch was added to 300 mL of deionized water, and stirred to heat to 95 °C, and the paste was magnetically stirred for 50 min; after gelatinization, 0.1 g of alpha-amylase was added, and the reaction was continued at 95 °C for 1.8 h, and then the temperature was raised to 100 °C for 10 min to inactivate the enzyme; after inactivation, centrifugation (4000 rpm, 10 min) was performed, and the precipitate was collected and dried in a freeze dryer at -50 °C until constant weight (about 24 h), and then ground and passed through a 100 mesh sieve to obtain pretreated starch. 100 g of pretreated starch, 10 g of glycerol, 7 g of N-(2,3-epoxypropyl)-dodecanoyl aspartate, and 5 g of 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride were added to a high-speed mixer, and mixed at 1000 rpm for 25 min at 100 °C; after mixing, 0.1 g of ammonium persulfate and 0.04 g of ascorbic acid were added, and mixing was continued for 15 min; the mixture was transferred to a twin-screw extruder, and the barrel temperature was set to 140 °C and the screw rotation speed was set to 250 rpm, and the mixture was melt blended for 5 min, and then cooled by water to obtain starch-based composite masterbatch; the masterbatch was dried in a vacuum drying oven at 80 °C for 4 h, and then added to a film blowing machine, and the die temperature was set to 160 °C, the blowing ratio was set to 2.5:1, and the pulling speed was set to 5 m / min, and a film with a thickness of 0.10 mm was blown.

[0048] Example 2 The specific implementation is the same as in Example 1, except that the preparation of N-(2,3-epoxypropyl)-dodecanoyl aspartate: L-aspartic acid 12 g, dodecanoyl chloride 14 g, anhydrous tetrahydrofuran 60 mL, reaction at 4 °C for 3 h; NaHCO3 aqueous solution 120 mL, filter and dry to obtain N-dodecanoyl-L-aspartic acid 12 g. The subsequent steps are the same as in Example 1, and the target product is finally obtained. Preparation of 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride: 3-chloro-2-hydroxypropyl trimethylsilane 18 g, anhydrous ethanol 60 mL, allyl alcohol 6 g, NaOH 2.5 g to adjust pH = 11, reaction at 72 °C for 8 h; target product is obtained by distillation under reduced pressure. Preparation of starch-based degradable food packaging bag: pretreated starch 120 g, glycerol 12 g, N-(2,3-epoxypropyl)-dodecanoyl aspartate 9 g, 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride.

[0049] Example 3 The specific implementation is the same as example 1, except that the preparation of N-(2,3-epoxypropyl)-dodecanoyl aspartate: L-aspartic acid 8 g, dodecanoyl chloride 10 g, anhydrous tetrahydrofuran 40 mL, 1℃ reaction for 5 h; NaHCO3 aqueous solution 80 mL, filtration and drying to obtain N-dodecanoyl-L-aspartic acid. The subsequent steps are the same as example 1, and finally the target product is obtained. Preparation of 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride: 3-chloro-2-hydroxypropyl trimethylsilane 12 g, anhydrous ethanol 40 mL, allyl alcohol 4 g, NaOH 1.5 g to adjust pH=11, 70℃ reaction for 6 h; vacuum distillation to obtain the target product. Preparation of starch-based degradable food packaging bag: pretreated starch 80 g, glycerol 8 g, N-(2,3-epoxypropyl)-dodecanoyl aspartate 5 g, 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride 3 g.

[0050] Comparative example 1 The specific implementation is the same as example 1, except that the preparation step: take potato starch 100 g, add deionized water 300 mL, gelatinize at 94℃ for 50 min; add α-amylase 0.1 g, after 2 h, inactivate the enzyme, centrifuge, freeze-dry, and crush to obtain pretreated starch. Add pretreated starch 100 g, glycerol 10 g to a high-speed mixer and mix for 30 min; add ammonium persulfate 0.1 g, ascorbic acid 0.04 g, and continue to mix for 10 min; twin-screw extrusion (130℃, 300 rpm) to obtain granules, which are dried and then blown into a film (160℃, 2.5:1) to obtain a film (without modifier).

[0051] Comparative example 2 The specific implementation is the same as example 1, except that 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride is not added.

[0052] Comparative example 3 The specific implementation is the same as example 1, except that N-(2,3-epoxypropyl)-dodecanoyl aspartate is not added.

[0053] Performance test The starch-based degradable food packaging bags prepared in examples 1-3 and comparative examples 1-3 above are tested for performance according to the following method: 1. Water resistance test: according to GB / T 1034-2008 standard, cut the film sample into a square of 50 mm×50 mm, rinse the surface with deionized water for 3 times, and then dry to constant weight (recorded as initial mass m0); immerse the sample completely in 25℃ deionized water, take it out after 24 h, quickly absorb the surface water with filter paper, and weigh (recorded as m1), calculate the water absorption rate (water absorption rate=(m1-m0) / m0×100%).

[0054] 2. Mechanical property test: according to GB / T 1040.2-2006 standard, the film was cut into dumbbell-shaped samples (gauge length 25 mm, width 6 mm, thickness 0.01-0.02 mm), using a universal material testing machine (tensile rate 50 mm / min), the maximum load (F_max) and elongation at break (ε=(L-L0) / L0x100%, L0 is the initial gauge length, L is the gauge length at break) of the sample were tested, 5 samples were tested for each group and the average value was taken.

[0055] 3. Thermal stability test: using a thermal gravimetric analyzer (TGA), the film sample was ground into powder (passed through a 200 mesh sieve), 10 mg was weighed and placed in an aluminum crucible, under a nitrogen atmosphere (flow rate 50 mL / min), the temperature was raised from 25°C to 600°C at a rate of 10°C / min, the change curve of sample mass with temperature was recorded, and the temperature (T s ) at which 5% weight loss occurred was taken as the thermal decomposition onset temperature.

[0056] 4. Antibacterial property test: using the agar diffusion method, Escherichia coli (ATCC 25922) was inoculated in LB liquid medium and cultured at 37°C for 12 h (OD 600 =0.8-1.0), diluted to 1x10 5 CFU / mL; the film sample was cut into a circle with a diameter of 60 mm, and was sterilely placed on an LB agar plate coated with 100 μL of bacterial suspension (3 samples per plate); after 18 h of incubation at 37°C, the diameter of the inhibition zone was measured with a vernier caliper (average value of 3 samples).

[0057] 5. Degradability test: according to GB / T 38082-2019 standard, the film sample was cut into 2 mm x 2 mm pieces (10 4 CFU / g of Bacillus subtilis and 10 4 CFU / g of Aspergillus niger were added per gram of sample), mixed with compost (matured pig manure compost, moisture content 60%, C / N=25:1) at a mass ratio of 1:10, and placed in a constant temperature and humidity incubator (humidity 60%) at 58°C for 180 d; samples were taken every 30 d, the surface residual compost was washed off with deionized water, and the sample was dried at 105°C to constant weight (recorded as m_t), and the degradation rate was calculated (degradation rate=(m0-m_t) / m0x100%, m0 is the initial dry weight).

[0058] 6. Performance test results: Table 1: Performance test results of each example and comparative example ; As can be seen from Table 1, the examples 1-3 significantly improve the comprehensive performance of the starch-based degradable food packaging material through the synergistic effect of two brand-new modified compounds (N-(2,3-epoxypropyl)-dodecanoyl aspartate and 3-(allyloxy)-2-hydroxypropyl trimethylsilyl chloride), effectively solving the technical problems of poor water resistance, insufficient mechanical properties, single function, weak combination of modified agent and starch, and easy residue of harmful substances after degradation of traditional starch-based materials.

[0059] In terms of water resistance, the water absorption rate of Comparative Example 1 (without modified agent) is as high as 12.6%, while the water absorption rate of Examples 1-3 is only 3.8%-5.1%, with a decrease of more than 60%. This is because the two modified agents respectively reduce the material surface polarity through long-chain alkyl (dodecanoyl) and trimethylsilyl (SiHAC), and the epoxy group (CAO) forms covalent cross-linking with the hydroxyl group of starch, reducing the hydrogen bonding between starch molecular chains, significantly improving the hydrophobicity of the material, and solving the problem of poor water resistance of traditional starch-based materials due to strong hydrophilicity.

[0060] In terms of mechanical properties, the tensile strength of Comparative Example 1 is only 24.6 MPa, and the elongation at break is 115%, while the tensile strength of Examples 1-3 is increased to 48.7-55.1 MPa, and the elongation at break is increased to 240%-280%. This is because the two modified agents and starch molecules form a three-dimensional network structure through covalent bonds (epoxy ring opening cross-linking) and hydrogen bonds (hydroxyl, carboxyl interaction), enhancing the structural strength and toughness of the material, overcoming the problem of insufficient mechanical properties of traditional starch-based materials due to weak intermolecular forces.

[0061] In terms of single function, Comparative Example 1 has no antibacterial property (bacteriostatic circle 0 mm), while the bacteriostatic circle diameter of Examples 1-3 reaches 27.4-29.2 mm, and the thermal decomposition onset temperature is increased from 165℃ of Comparative Example 1 to 208-220℃, indicating that the material has antibacterial property and thermal stability. Traditional modified agents (such as citric acid ester) can only improve single performance (such as plasticization), while the present application designs multiple functional groups (hydrophobic / cross-linking of CAO, antibacterial / hydrophobic of SiHAC) through two modified agents, giving the material multiple functional characteristics, solving the problem of single function.

[0062] The problem of weak combination of the modifier and starch is particularly prominent in Comparative Example 2 (only CAO is added) and Comparative Example 3 (only SiHAC is added): the water absorption rate of Comparative Example 2 (8.9%) is better than that of Comparative Example 1, but is still significantly higher than that of Examples 1-3; the tensile strength (38.9 MPa) and thermal decomposition temperature (190℃) of Comparative Example 3 are also lower than those of the examples. This shows that the interaction of a single modifier with starch (such as only covalent crosslinking or only hydrophobicity) is limited, while in the present application, the two modifiers form a tighter interface combination through the synergistic crosslinking of epoxy groups (CAO) and allyloxy groups (SiHAC), the hydrogen bonding of hydroxyl groups and carboxyl groups, which significantly improves the compatibility of the modifier and starch.

[0063] In terms of degradability, the 180d degradation rate of Comparative Example 1 is only 22.3%, and Comparative Examples 2 (45.1%) and 3 (58.7%) have improved, but are still far lower than the 95.8%-97.2% of Examples 1-3. Traditional modifiers often contain non-degradable petroleum-based components (such as long-chain alkyl groups, petroleum ether), while the modifier of the present application uses natural amino acids (L-aspartic acid), siloxanes (trimethylsilane) and other renewable resources as raw materials, and only contains elements such as carbon, hydrogen, oxygen and silicon in the molecular structure, which can be completely decomposed by microorganisms into water and carbon dioxide, avoiding the problem of residual harmful substances after degradation of traditional modified materials.

[0064] In summary, Examples 1-3 achieve a breakthrough improvement in water resistance, mechanical properties, functional diversity, binding force and degradability through the synergistic effect of two new modified compounds, effectively solving the core application bottleneck of traditional starch-based degradable packaging materials.

[0065] The above examples only express several embodiments of the present application, and the description is more specific and detailed, but it cannot be understood as limiting the scope of the present patent. It should be noted that for ordinary skilled persons in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, which are within the scope of protection of the present application.

Claims

1. A starch-based biodegradable food packaging bag, characterized in that: The invention comprises the following raw materials in parts by weight: Pretreated potato starch: 80-120 parts by weight; Glycerol: 8-12 parts by weight; N-(2,3-Epoxypropyl)-dodecanoyl aspartate: 5-9 parts by weight; 3-(Allyloxy)-2-hydroxypropyltrimethylsilyl chloride: 3-7 parts by weight; Ammonium persulfate: 0.08-0.15 parts by weight; Ascorbic acid: 0.02-0.06 parts by weight; The preparation method of N-(2,3-epoxypropyl)-dodecanoyl aspartic acid ester includes: A1, mixing L-aspartic acid and anhydrous tetrahydrofuran, adding dodecanoyl chloride and reacting at 0-5°C, adding NaHCO3 aqueous solution, filtering and drying to obtain N-dodecanoyl-L-aspartic acid; A2, dissolving N-dodecanoyl-L-aspartic acid in acetone, adding epichlorohydrin, reacting at 60-64°C under the action of K2CO3, precipitating with ether, washing, and vacuum drying.

2. The starch-based biodegradable food packaging bag according to claim 1, characterized in that: In step A1, the reaction time at 0-5°C is 3-5h.

3. The starch-based biodegradable food packaging bag according to claim 1, characterized in that: In step A2, the reaction time is 4-6 hours at 60-64°C; the vacuum drying temperature is 40-42°C and the time is 12-14 hours.

4. The starch-based biodegradable food packaging bag according to claim 1, characterized in that: The preparation method of 3-(allyloxy)-2-hydroxypropyltrimethylsilyl chloride comprises the following steps: B1, mixing 3-chloro-2-hydroxypropyltrimethylsilane with anhydrous ethanol, adding allyl alcohol, then adding NaOH to adjust the pH to 10-11, and stirring at 70-72° C. for reaction; B2, distilling under reduced pressure after the reaction is completed, and drying with anhydrous sodium sulfate.

5. The starch-based biodegradable food packaging bag according to claim 4, characterized in that: In step B1, the reaction time is 5-10 h with stirring at 70-72°C.

6. The starch-based biodegradable food packaging bag according to claim 4, characterized in that: In step B2, the temperature of the reduced pressure distillation is 60-64° C.; and the drying time is 2-4 h.

7. A method for preparing a starch-based biodegradable food packaging bag according to any one of claims 1 to 6, characterized in that the steps include: S1. Take potato starch, add deionized water, and gelatinize at 94-96°C with magnetic stirring; add α-amylase to react, inactivate the enzyme, and centrifuge. The resulting precipitate is freeze-dried to constant weight, crushed, and sieved to obtain pretreated starch; S2, adding pretreated starch, glycerol, N-(2,3-epoxypropyl)-dodecanoyl aspartate, and 3-(allyloxy)-2-hydroxypropyltrimethylsilyl chloride into a high-speed mixer and mixing to obtain a blend; S3. Add ammonium persulfate and ascorbic acid to the blend and continue mixing; transfer to a twin-screw extruder, melt blend, and then water-cool and pelletize to obtain a starch-based composite masterbatch. After the masterbatch is dried in a vacuum drying oven, it is added to a film blowing machine and blown into a film.

8. The preparation method according to claim 7, characterized in that In step S1, the gelatinization time is 40-60 minutes; the reaction time of adding α-amylase is 1.5-2 hours.

9. The preparation method according to claim 7, characterized in that In step S2, the mixing time is 20-30 min.

10. The preparation method according to claim 7, characterized in that In step S3, the mixing is continued for 10-20 minutes; the barrel temperature of the twin-screw extruder is 130-150° C., and the screw speed is 200-300 rpm.